2013
DOI: 10.1111/apt.12204
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the GerdQ questionnaire for the diagnosis of gastro‐oesophageal reflux disease

Abstract: SUMMARY BackgroundThe diagnosis of gastro-oesophageal reflux disease (GERD) remains a challenge as both invasive methods and symptom-based strategies have limitations. The symptom-based management of GERD in primary care may be further optimised with the use of a questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
186
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(203 citation statements)
references
References 27 publications
5
186
1
11
Order By: Relevance
“…In our study, sensitivity and specificity compared with former clinical diagnosis was of 54% and 72%, respectively. More recently, Jonasson et al, 14 in the validation study for questionnaire in 169 patients with GERD (93% erosive) found higher sensitivity (78%) with lower specificity (50%). This difference can be explained since in this study, authors were highly biased by referrals and prevalence of erosive GERD.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, sensitivity and specificity compared with former clinical diagnosis was of 54% and 72%, respectively. More recently, Jonasson et al, 14 in the validation study for questionnaire in 169 patients with GERD (93% erosive) found higher sensitivity (78%) with lower specificity (50%). This difference can be explained since in this study, authors were highly biased by referrals and prevalence of erosive GERD.…”
Section: Discussionmentioning
confidence: 97%
“…Postprandial distress syndrome (PDS) was defined as the presence of symptoms with early satiation and/or postprandial fullness (present for last 3 months and onset at least 6 months prior to diagnosis). Reflux symptoms were evaluated with the gastroesophageal reflux disease questionnaires (GerdQ) [13,14]. The cut-off score of GerdQ was set at 8 as reported previously [14].…”
Section: Methodsmentioning
confidence: 99%
“…Developed as an exploratory part of the DIAMOND study, this simple self administered 6-item questionnaire showed a fair diagnostic accuracy when compared to diagnosis of GERD made by EGD, pH-monitoring or response to PPI treatment if AET in pH-monitoring was borderline, with a sensitivity of 65%, specificity of 71% and positive predictive value (PPV) of 80% using a cut-off value of 8 or higher (range 0-18) (11,12). These results were reproduced in later studies (22). Two recent European multicentre prospective studies concluded that patient management based on GerdQ score was not only non-inferior in achieving patient satisfaction but also cheaper than a more classical strategy, based on prompter EGD and pH monitoring (13,14).…”
Section: Discussionmentioning
confidence: 69%